STUDI PEMIKIRAN PENDIDIKAN SA‘ID ISMA‘IL ‘ALI TENTANG DASAR-DASAR PENDIDIKAN ISLAM - ROSIDIN ROSIDIN (STAI Ma'had Aly Al-Hikam Malang, 2020)
The crises and problems in Islamic education theories and practices can be solved through the thought of contemporary Islamic education experts. This paper examines Sa’id Isma’il ‘Ali’s thoughts on the Fundamentals of Islamic Education from an epistemological perspective involving three academic problems: sources, objects and methods of Islamic education. The contributions of the Formulation of Sa’id Isma’il ‘Ali’s thoughts on the Fundamentals of Islamic Education adopts the reasoning method of Islamic Law (Fiqh) and Islamic Jurisprudence (Usul al-Fiqh) scholars. More comprehensive than the ideas of other thinkers who tend to be general, i.e. the Qur’an and al-Sunnah. In terms of sources, the Fundamentals of Islamic Education are divine (Ilahi) and humane (Bashari). In terms of objects, the Fundamentals of Education aims to realize the content of the Holy Qur’an specifically and the teachings of Islam generally. In terms of methods, the Fundamentals of Islamic Education involves empirical, logical and intuitive methods.ABSTRAKKrisis dan problem yang mendera pendidikan Islam dapat dicarikan alternatif solusinya melalui kajian pemikiran pakar pendidikan Islam kontemporer. Tulisan ini menelaah pemikiran Sa’id Isma’il ‘Ali tentang Dasar-Dasar Pendidikan Islam dari perspektif epistemologis yang melibatkan tiga rumusan masalah: sumber, objek dan metode pendidikan Islam. Adapun kontribusi keilmuan Sa’id Isma’il ‘Ali tentang Dasar-Dasar Pendidikan Islam mengadopsi metode panalaran ulama Fikih dan Ushul Fikih. lebih komprehensif dibandingkan gagasan para pemikir lain yang cenderung general, yaitu al-Qur’an dan al-Sunnah. Dari segi sumber, Dasar-Dasar Pendidikan Islam bersifat Ilahi (ketuhanan) dan Basyari (kemanusiaan). Dari segi objek, Dasar-Dasar Pendidikan bertujuan merealisasikan isi kandungan al-Qur’an secara khusus dan ajaran Islam secara umum. Dari segi metode, Dasar-Dasar Pendidikan Islam melibatkan metode empiris, logis dan intuitif.